Potencialização da atividade larvicida das toxinas de Bacillus thuringiensis pelo inibidor de tripsina de sementes de Albizia lebbeck contra larvas do gênero Aedes - Tabosa, Pedro Matheus Sousa (2023)
Aedes aegypti and Ae. albopictus have attracted worldwide attention because they are responsible for the transmission of several viruses, such as dengue fever, chikungunya and Zika. There are several programs and strategies to avoid the increase in number of cases of these diseases, such as by combating vectors. Natural molecules, such trypsin inhibitors, with no or low toxicity to non-target organisms and greater biodegradability can be used to reduce the populations of these insects. Thus, the objective of this work is to evaluate the potentiation of Bacillus thuringiensis (Bt) toxins by a trypsin inhibitor from Albizia lebbeck (L.) Benth seeds on the development of Ae. aegypti and Ae. albopictus, as well as to evaluate the toxicity on non-target organisms. The trypsin inhibitor AlsTI purified from A. lebbeck seeds was able to inhibit trypsin and intestinal proteases of Ae. aegypti and Ae. albopictus larvae. The AlsTI was confirmed as a single band on SDS-PAGE under non-reducing conditions with an approximate molecular mass of 20 kDa and partial sequencing data showed that this inhibitor belongs to the Kunitz- type group. In addition, the trypsin inhibitor showed resistance when subjected to different conditions of temperature, pH and reducing conditions. Bt toxins demonstrated toxicity (LC50 and LC20) against the larvae of both species and the midgut damage was confirmed by histological analyses. In parallel, AlsTI was able to increase the mortality of Ae. aegypti larvae when combined with the Bt toxins about two to three times, but the same did not happen for the Ae. albopictus. In non-target organisms, the toxicity of these molecules was not observed when tested combined or separately against Artemia sp. nauplii. However, a 20% mortality in Danio rerio embryos both in Bt toxins and in combination with the inhibitor was observed. The results obtained in this work may be used in the production of new bioinsecticides against insects that transmit diseases of the genus Aedes.